Lenguaje y experiencia en la mística judía - Paz Blanco, María Rosario de (Universidad Complutense de Madrid, Servicio de Publicaciones, 2008)
"Language and experience in Jewish mysticism" is a work in which, after dealing with an approach of the so-called mysticism and its ways of study, its physical, psychic perspectives are explored, its phenomenological description, its stages, its ways and a slight characterization of the types of mysticism from the viewpoint of religion. By comparison, the Jewish mysticism is placed in what it has in common and peculiar language notion and its performing function in the experiential world in Jewish traditional texts, that is, the limit and the emptiness as shown in the letter, the world and discourse. The text is, in Jewish tradition and in any other religion, an ontological foundation, not only in the orthodox-Torah and Talmud- but also the hidden and the cabalistic. The mystic experience is present and it also nourishes the root of the very text and cultural forms of the Jewish Community. The text will be the roots and top of reality in the Sefirotico tree. Finally, the body of the mystic is changed into a text and speaks of what should-be-not mentioned. The metaphors and symbolism, which appear in the beautiful literature of the Jewish tradition, allow to appreciate the non-stop flowing of the emptiness, ultimate foundation of the mystic, and also ordinary experience. The analysis of the four commentaries of "Cantar de los Cantares" a masterpiece text, says so. The text embodies the whole society, as a law that articulates closely with de mystic saying, giving sense, programme and protagonist to the historical experience of the Jewish. Our intention is to connect the findings of universal echo that the Jewish mysticism contribute to present-day questions prompted in the political and social fields. Our expectations are to show that the Jewish mysticism and its peculiar point of view is a rich inspiration for philosophers, writers, therapists and endless list of etceteras. The texts are not only related to other mysticism but also, what they bring out is by no means fossilized, nonetheless, it is utterly alive, suggesting and worth taking into account.